An inducible fusaric acid tripartite efflux pump contributes to the fusaric acid resistance in Stenotrophomonas maltophilia. - Rouh-Mei Hu; Sih-Ting Liao; Chiang-Ching Huang; Yi-Wei Huang; Tsuey-Ching Yang (PLoS ONE, 2012)
BACKGROUND: Fusaric acid (5-butylpicolinic acid), a mycotoxin, is noxious to some microorganisms. Stenotrophomonas maltophilia displays an intrinsic resistance to fusaric acid. This study aims to elucidate the mechanism responsible for the intrinsic fusaric acid resistance in S. maltophilia. METHODOLOGY: A putative fusaric acid resistance-involved regulon fuaR-fuaABC was identified by the survey of the whole genome sequence of S. maltophilia K279a. The fuaABC operon was verified by reverse transcriptase-PCR. The contribution of the fuaABC operon to the antimicrobial resistance was evaluated by comparing the antimicrobials susceptibility between the wild-type strain and fuaABC knock-out mutant. The regulatory role of fuaR in the expression of the fuaABC operon was assessed by promoter transcription fusion assay. RESULTS: The fuaABC operon was inducibly expressed by fusaric acid and the inducibility was fuaR dependent. FuaR functioned as a repressor of the fuaABC operon in absence of a fusaric acid inducer and as an activator in its presence. Overexpression of the fuaABC operon contributed to the fusaric acid resistance. SIGNIFICANCE: A novel tripartite fusaric acid efflux pump, FuaABC, was identified in this study. Distinct from the formally classification, the FuaABC may constitute a new type of subfamily of the tripartite efflux pump.